Paciente de sexo masculino de 68 años de edad con cáncer de próstata e hipertensión. - Fuentes Vera, Islandia Anabell (2021)
Cancer is the second leading cause of death in Latin America. In 2018, 3.8 million cases were diagnosed and 1.4 million people died from this disease. If no action is taken, it is projected that by 2030 the number of people diagnosed with cancer will increase by 32% to more than 5 million people per year, as the population is aging, lifestyles continue to change and the exposure to hazardous components. Nutrition therapy in cancer patients will help maintain a healthy weight, prevent loss of lean body mass, protect immune function, and decrease side effects during and after treatment. The guidelines of the European Society for Clinical Nutrition and Metabolism recommend considering the energy requirements of cancer patients equal to those of healthy people. High blood pressure is a chronic disease in which the blood vessels have persistently high tension, which can damage them. Blood pressure is the force that blood exerts against the walls of the arteries as it is pumped by the heart. In the 90's the US National Institute of Health developed a proposal to regulate hypertension through diet, the acronym DASH is named Dietary Approaches to Stop Hypertension, this diet includes increasing the content of micronutrients such as potassium, calcium and magnesium, the consumption of fruits and vegetables and reduce the consumption of sodium and saturated fat.